COMPUTATIONAL FLUID DYNAMIC (CFD) INVESTIGATION ON PERFORMANCE OF PARABOLIC TROUGH COLLECTOR (PTC) USING OIL BASED NANOFLUID - Ahmad Fauzi, Muhamad Faiz Danial (IRC, 2021)
Solar energy system has been researched since it is a good replacement or alternative for unrenewable energy such as fossil fuels and biomass.